Viability of ward tribunals in dispensation of criminal justice in mainland Tanzania: A survey of Bukoba district in Kagera region - Uiso, Charles Samson (Mzumbe University, 2023)
A Dissertation Submitted in Partial Fulfillment of the Requirements for Award of the Degree of Master of Laws (LL.M) in Constitutional and Administrative Law of Mzumbe University